After Effects compositing tools. (8th July 2020) - Okemow, Stefanie Joelle
Abstract: This paper provides information to enhance medical animations, by detailing the uses and techniques involved with layer modes, track mattes and layer masks in Adobe After Effects. Much like Photoshop and static two-dimensional images, layer modes in After Effects allow for the layer above to interact with the layer below in terms of light and colour balance. Track mattes can be rendered out in addition to your base image sequence and can remove the need for rotoscoping. In addition to rotoscoping more complicated areas of your footage, layer masks can also be used in conjunction with solids to add colour and gradients to your animations. The example file works with still rendered 3D images but the principles apply to image sequences as well. This article assumes a basic understanding of the After Effects user interface, creating compositions and importing files. Overall, the article will aid in the creation of more visually appealing medical animations.